Studi Meta-Analisis Dampak Penggunaan Vidio Pembelajaran Terhadap Peserta Didik - Alam Tarlam (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
This study aims to analyze the impact of using video media on the effectiveness learning through a meta-analysis approach. Data were collected from 10 relevant previous studies to identify patterns and trends in the use of video media as a learning aid. The analysis results indicate that video media has a significant positive impact on students' learning outcomes. The average pretest score before using video media was 55.75%, while the average posttest score increased significantly to 86.33%. Additionally, student attendance rates increased by 30.25%, suggesting that video media not only enhances conceptual understanding but also boosts learning motivation. These findings confirm that integrating video media into learning can make the learning process more interactive, engaging, and effective, thereby supporting the improvement of religious education quality at various levels.